New onset neurologic events in people with COVID-19 in 3 regions in China. (15th September 2020) - Xiong, Weixi; Mu, Jie; Guo, Jian; Lu, Lu; Liu, Dan; Luo, Jianfei; Li, Nian; Liu, Jing; Yang, Dan; Gao, Hui; Zhang, Yingying; Lin, Mintao; et al.
Abstract : Objective: To investigate new-onset neurologic impairments associated with coronavirus disease 2019 (COVID-19). Methods: A retrospective multicenter cohort study was conducted between January 18 and March 20, 2020, including people with confirmed COVID-19 from 56 hospitals officially designated in 3 Chinese regions; data were extracted from medical records. New-onset neurologic events as assessed by neurology consultants based on manifestations, clinical examination, and investigations were noted, in which critical events included disorders of consciousness, stroke, CNS infection, seizures, and status epilepticus. Results: We enrolled 917 people with average age 48.7 years and 55% were male. The frequency of new-onset critical neurologic events was 3.5% (32/917) overall and 9.4% (30/319) among those with severe or critical COVID-19. These were impaired consciousness (n = 25) or stroke (n = 10). The risk of critical neurologic events was highly associated with age above 60 years and previous history of neurologic conditions. Noncritical events were seen in fewer than 1% (7/917), including muscle cramp, unexplained headache, occipital neuralgia, tic, and tremor. Brain CT in 28 people led to new findings in 9. Findings from lumbar puncture in 3 with suspected CNS infection, unexplained headache, or severe occipital neuralgia were unremarkable. Conclusions: People with COVID-19 aged over 60 and with neurologic comorbidities were at higher risk of developing critical neurologic impairment, mainly impaired consciousness and cerebrovascular accidents. Brain CT should be considered when new-onset brain injury is suspected, especially in people under sedation or showing an unexplained decline in consciousness. Evidence of direct acute insult of severe acute respiratory syndrome coronavirus 2 to the CNS is lacking.